Renovação Carismática Crioula: uma leitura do papel do animador litúrgico na Renovação Carismática Católica em Juiz de Fora sob a luz de Sacrosanctum Concilium 37-39 - Simões, Julio Eduardo dos Santos Ribeiro (2009)
This dissertation aims to investigate the mechanisms of liturgical adaptation happening on the Roman Catholic Church in Brazil using a punctual investigation of the Commentator (or Animator) liturgical function on the location of Juiz de Fora MG, inserted on the ecclesial context known as Renovação Carismática Católica (a local translation and adaptation of the American Charismatic Renewal) The prime hypothesis is that the historical development of Brazil as a State allowed the arising of a cultural expression common to this country and also the Cultural Subcontinent in which it is inserted, that is Latin and Caribbean America. Trying to confirm this hypothesis, Creoleness (or Creolization) theory, composed on Caribbean America, is used to enlighten the object (which is the Litugical Animator in charge of it s functions), expanding the creolization question far beyond from mere literary theory, reaching the ritual language level. The cited theory breaks with the illusions of purity when proposes a Latin American notion not as a chunking between cultural and ritual identities, but as a meeting of these formed from loans constituted over the centuries of coexistence between cultures on the cited subcontinent. This work is justified on the necessity of the Church s academic and pastoral environments to enplane what is Brazilian culture in a more valid manner, not resorting generalizing subterfuges, that have been producing a image and self-image of Brazilian church and culture as a relatively sealed values overlapping. The text was build from a deliberated option in favour of comparison between texts about Brazilian culture and the ones about cultural adaptation on Brazil, establishing similarities and disparities between both. On a second overview, there is a comparison between these and the directives on magisterial documents concerning adaptation. These texts, we suppose, guide the liturgical practice in Brazil, and at last overcomes a comparison between the proposed and delimited on the same texts and the practised by Comentator on concrete reality, using Renovação Carismática Católica as a model. Results suggest that the Comentator is correspondent to the cultural between existing between the winners rite (the white Christians) and the rites from the subdued peoples (the interbred mass), being the manifestation prime location of creoleness on Brazilian Catholic celebrations. Nevertheless, further research over the theme is necessary in order to confirm or refute this hypothesis.